Study on Geometric Composition Analysis Method of Plane Bar Structure - Lyu, Haoyu (Transactions on Engineering and Technology Research, 2024)
The analysis of the geometric composition of planar bar structures is of great importance to both civil engineering students and scholars. In this paper, the basic method of the geometrical composition of the planar member structure is described, and the geometric composition method of the system standard is given by combining the common method with a single method. Firstly, the methods and techniques involved in the existing literature are summarized, and these methods are comprehensively evaluated. Then, the analysis method of plane geometry composition and the standardization application flow are presented, including the analysis of difficulties and the solutions. Finally, the application of Equivalent Replacement method to solve the problem is illustrated by examples. This paper can help the relevant industry and scholars to solve the geometric composition of the planar bar structure more effectively and avoid some mistakes. It can also provide a standard process for beginners to solve problems such as ignoring rigid bodies.